2020
DOI: 10.1111/cen.14313
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenia in patients with hyperthyroidism: Systematic review and meta‐analysis

Abstract: Background and Objective Neutropenia, a low absolute neutrophil count (ANC), may be a sign of new‐onset hyperthyroidism. The aim of this systematic review and meta‐analysis was to provide the most reliable estimates of prevalence, degree and response to treatments of neutropenia in the pure hyperthyroidism setting. Methods A comprehensive literature search was performed in PubMed and Scopus databases for retrieving articles in English and non‐English languages reporting ANC values/neutropenic cases at presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 40 publications
3
24
1
Order By: Relevance
“…This study (3) showed a high prevalence (55%) of having at least one LFT abnormality in patients with newly diagnosed untreated hyperthyroidism. This is higher than previously reported prevalence of about 39% as reported in a previous review (2), although the range of LFT abnormalities in other reports spans 11 to 78% as referenced in the current study (3) . In this meta-analysis, the subset of patients with Graves' disease had a slightly higher prevalence of abnormal LFTs, at 60%.…”
Section: Commentarycontrasting
confidence: 75%
“…This study (3) showed a high prevalence (55%) of having at least one LFT abnormality in patients with newly diagnosed untreated hyperthyroidism. This is higher than previously reported prevalence of about 39% as reported in a previous review (2), although the range of LFT abnormalities in other reports spans 11 to 78% as referenced in the current study (3) . In this meta-analysis, the subset of patients with Graves' disease had a slightly higher prevalence of abnormal LFTs, at 60%.…”
Section: Commentarycontrasting
confidence: 75%
“…2021, 11 495 with thyroidectomy [17], and anemia (microcytic and normocytic anemia) has been reported in almost 25-55% of the patient with thyroid hypothyroidism [9,13,18,19]. Similarly, earlier reports demonstrate the association of Graves's disease with anemia [17,20,21].…”
Section: Introductionmentioning
confidence: 98%
“…The symptoms and CK elevations in thyrotoxic myopathy could be resolved with the continuation of ATD and addition of analgesics, but this approach was not attempted in the present case. Laboratory abnormalities associated with hyperthyroidism, such as neutropenia and elevated transaminase, are usually normalized with ATDs, and they should not be regarded as contraindications to use ATDs [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%